Risk factors and effects of the morbus: COVID-19 through the biopsychosocial model and ecological systems approach to social work practice - Chigangaidze, Robert K. (Routledge, 2021)
Utilizing the biopsychosocial model and the ecological systems theory, this disquisition explores on the risk factors associated with the COVID-19 pandemic. The discourse shows the interconnectedness of biological, psychological, and social domains in expatiating on the COVID-19 pandemic. It calls for the need to strengthen the resilience of the global community in the face of health outbreaks such as COVID-19. It emphasizes on the perspectives that pandemics are managed before they emerge through building systems that are resilient. Thus, it appreciates the need for a therapeutic milieu as a building block to resilience. The article calls for the adoption of a developmental stance to analyzing health outbreaks and clinical issues. The adumbration shows the reciprocity effects of the health outbreak [macrocosms] and individual factors [microcosms]. To its end, the paper implies that COVID-19 is a call for integration toward effective health planning between social policy formulators, urban and rural planners, epidemiologists, development practitioners, clinicians, researchers to mention but a few. Ultimately, the paper calls for social workers to consider a developmental-clinical social work approach which helps foster “health in all policies” so as to build resilience against the morbus and limit the proliferation of diseases.